God, Desire, and Musical Narrative in the Isorhythmic Motet - Fast, Susan (Canadian University Music Review / Revue de musique des universités canadiennes, 1997)
This article examines the relationship between late Medieval narrative structure in French literature and music (specifically the isorhythmic motet) and how that structure was shaped by deeply held beliefs within Medieval culture, including the idea that a person's identity and desires were directed by God. A detailed analysis of the motet De bon espoir/Puis que la douce rousee/Speravi by Guillaume de Machaut is made to support the argument.